Diagnostic Yield of Bronchoscopic Alveolar Lavage Gene Xpert MTB/Rif in Smear Negative Clinico-Radiologically Suspected Case of Pulmonary Tuberculosis - Bista, Bidesh; Karmacharya, Niraj; Hari Ghimire, Ram; Shrestha, Pradeep; Poudel, Deepak; Kurumbang, Janer; Mahato, Manoj; Raj Mishra, Deebya (Journal of Nobel Medical College, 2022)
Background: Early diagnosis of pulmonary tuberculosis is difficult but dreaded complications like cavitations, abscess, disseminations and fibrosis of lung parenchyma can be avoided. Sputum microscopy is still the most available test for diagnosis of pulmonary tuberculosis but sustainable number of active cases remains undiagnosed via this method alone. In strong clinico-radiological pulmonary tuberculosis patients who are sputum scarce or sputum microscopy and sputum Xpert MTB/Rif negative broncho-alveolar lavage may provide superior sample for Gene Xpert MTB/Rif in diagnosis of Pulmonary Tuberculosis. Materials and Methods: Over 2 years period, patients with strong clinico-radiological suspicion of pulmonary tuberculosis who had sputum microscopy and sputum Xpert MTB/Rif negative were included in the study. Fibro-optic bronchoscopy was done for BAL Xpert MTB/Rif test. Base line demographic, clinical and radiological data were systematically analysedby SPSS software version 17. Results: 64 patients were included in the study with mean age 41 ± 10.52 years. The most common symptoms were cough, sputum production and weight loss with frequency of 58 (90.6%), 31 (48.4%) and 21 (32.11%) patients respectively. The most common CT scan findings were consolidation, cavitation and tree in bud pattern. BAL Xpert MTB/Rif was positive in 11 (17.18%) patients. According to the CT findings BAL Xpert MTB/Rif was most commonly present in patients presenting with cavitary lung disease. Conclusion: Eleven patients had BAL gene Xpert/Rif positive out of 64 patients who were sputum scarce or had both microscopy and sputum gene Xpert/Rif negative. Bronchoscopy BAL Xpert/Rif could provide an additional diagnostic test in these groups of patients.